1986
DOI: 10.1172/jci112402
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptor of human cerebral gliomas. Structure and function.

Abstract: The insulin receptor from human brain tumors of glial origin was examined for the first time using intact cells (from an established cultured human glioblastoma cell line) and partially purified solubilized membranes (from cultured cells and freshly isolated human brain tumors). The structure of the glial insulin receptor subunits was assessed by affinity cross-linking of 125I-insulin with the a-subunit of the receptor, neuraminidase treatment of the cross-linked receptor, behavior of the receptor on lectin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 34 publications
2
14
1
Order By: Relevance
“…The observation that glucose stimulates IGF-I transcription and IGF-IR/IR tyrosine phosphorylation in a dose-dependent manner in CT-2A cells in vitro lends additional support to the contention that IGF-I may act as an autocrine/paracrine growth factor in this experimental astrocytoma model. Although the IR is expressed in several regions of the adult brain and can be expressed in human gliomas (50,51), the insulin molecule itself is not produced in the central nervous system or in the central nervous system tumors and must cross the blood-brain barrier to reach the receptor. Furthermore, a recent study showed that less than 1% of peripherally given insulin enters the brain from the circulation in rodents (51).…”
Section: Discussionmentioning
confidence: 99%
“…The observation that glucose stimulates IGF-I transcription and IGF-IR/IR tyrosine phosphorylation in a dose-dependent manner in CT-2A cells in vitro lends additional support to the contention that IGF-I may act as an autocrine/paracrine growth factor in this experimental astrocytoma model. Although the IR is expressed in several regions of the adult brain and can be expressed in human gliomas (50,51), the insulin molecule itself is not produced in the central nervous system or in the central nervous system tumors and must cross the blood-brain barrier to reach the receptor. Furthermore, a recent study showed that less than 1% of peripherally given insulin enters the brain from the circulation in rodents (51).…”
Section: Discussionmentioning
confidence: 99%
“…The a-subunits contain the extracellular li gand binding site whereas the P-subunits con tain a transmembrane domain which induces intracellular tryosine kinase activity [29,30], Recent studies have suggested furthermore that the IGF-1 receptor can be a hybrid com posed of an insulin a/p-heterodimer, forming a heterotetrameric holoreceptor complex [29][30][31][32][33][34][35][36]. Despite the fact that insulin receptors and IGF-1 receptors are encoded from different genes they are structurally homologous [37], It is believed that this homology allows insulin to bind to the IGF-1 receptor -although with less affinity than IGF-1 [6,29,38,39], Binding of insulin and IGF-1 with the receptor's a-subunit initiates a receptor-me diated signaling process on tyrosine residues by autophosphorylation of the P-subunit [28,31,[40][41][42]. This leads to a series of biological effects e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although insulin receptors are expressed by cultured rat astrocytes (Schechter & Yanovitch 1999), the presence of this receptor in glial cells in situ has never been reported. Insulin binding sites have only been described in freshly isolated human brain tumors of glial origin (Grunberger et al 1986). Here, we have shown by an immunohistochemical approach that insulin receptors are present in numerous cells in the area bordering the third ventricle ( Fig.…”
Section: Resultsmentioning
confidence: 99%